Mortalidade de crianças de 0 a 14 anos em decorrência de acidentes de trânsito no Brasil - Campos, Cintia Isabel de (2014)
Traffic in large cities has become a challenge for the people who live there. In addition to economic and environmental damage, traffic chaos is responsible for countless victims annually, making it a leading cause of death worldwide. Among these victims, children between 0 and 14 suffer injuries due to traffic accidents as a leading cause of death. Only in Brazil, there are about 2,000 deaths involving children between the ages of 0 and 14 each year. The child is vulnerable in traffic due to immaturity and physical characteristics of this group, so it is necessary specific and targeted studies that support the government regarding the decision making and implementation of strategic actions to mitigate such a scenario. Thus, this study presents the scenario of traffic fatalities involving children in Brazilian traffic through indicators, as well as a comparison with socioeconomic indicators and the international scenario. The methodology included the calculation of primary indicators for all states, the geographical distribution of these rates, a comparison with the reality of other countries and the correlation of mortality indicators with socioeconomic ones. The countries chosen for the comparison with the Brazilian reality were those present in human development groups classified as: very high, high, and the ones which have similar or higher human development groups than the Brazilian scenario, and the ones which provide data for the calculation of indicators of mortality. In general, the Brazilian scenario is positive, since the rates are generally a decreasing curve. When considering economic development in relation to accidentality involving children, there was a negative and moderate correlation between mortality rates and GDP per capita for each state where performed. The correlations with Human Development Index (HDI) considering the year of the indicators showed a positive relationship. In international comparison, the indices showed a general decreasing trend in global accidentality rates, except in a few countries.